Psycholinguistic Study Analysis Of The Influence Of Age And Learning Experience On Students' Arabic Language Ability/ Analisis Studi Psikolinguistik Pengaruh Usía dan Pengalaman Belajar terhadap Kemampuan Berbahasa Arab Siswa - Ilvi Tamarisa Syarova; Dainunah Lillahi Wahdah; Tatang Tatang (Jurnal Bahasa Arab, 2026)
This study aims to explore the influence of age and learning experiences on Arabic language proficiency among 8th-grade students at an Islamic junior high school (MTS). The research adopts a qualitative approach with a single case study design. The primary data collection method employed is semi-structured interviews with a purposively selected student. The interview focuses on the student's experiences learning Arabic since elementary school, challenges faced in learning Arabic at the junior high school level, and the impact of age on the student's Arabic language skills. The findings reveal that learning Arabic from an early age, primarily focused on introducing vocabulary and the Arabic alphabet (hijaiyyah), provides a strong foundation for initiating Arabic language acquisition. However, major challenges emerge at the junior high school level, particularly in translating sentences and understanding the rules of nahwu and shorof (Arabic grammar). The student also expressed that learning experiences outside the classroom have contributed little to their Arabic proficiency due to the lack of opportunities to practice Arabic in daily life. Strategies to overcome these difficulties include expanding vocabulary and gaining a deeper understanding of Arabic grammar rules. This study highlights the importance of comprehensive Arabic language instruction from an early age and the need to create opportunities for students to practice Arabic in more natural contexts.